Sea-ice thickness evolution in ross and weddell seas in the period 1992-2008, estimated by ist algorithm using ssm/i brightness temperatures - G. Aulicino; G. Fusco (IGS - International Glaciological Society (Cambridge), 2011)
In polar regions, interactions between atmosphere and ocean are strongly influenced by presence/absence of the ice cover and by its thickness, hindering sensible heat fluxes and preventing latent heat loss. Since satellite passive microwave observations became available in the 1970s, significant progress has been made in the study of snow depth and sea-ice concentration and extent in these regions. In this work, a new algorithm (IST- Ice and Snow Thickness) has been implemented to estimate sea ice and snow thickness in Antarctica from SSM/I brightness temperatures, by using two ice classification parameters based on microwave polarization and spectral gradient information. Open water, snow presence and thin ice are recognized using a sequence of combined thresholds. Sea-ice results were validated with in situ sea-ice thickness data coming from NIC-NCDC campaigns (in the year 1994) and from Aspect project campaigns (1992–2004).